ACTINOBACTERIA PENGHASIL ANTIFUNGI ASAL RIZOSFER TEGAKAN KAYU PUTIH HUTAN WANAGAMA I YOGYAKARTA: ISOLASI, OPTIMASI DAN KARAKTERISASI ACTINOBACTERIA SERTA ISOLASI SENYAWA ANTIFUNGI - ALIMUDDIN, ALIMUDDIN; Asmara, Widya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research was to characteriz e of Actinobacteria isolate and evaluate their diversity and potential in vitro with ability in controlling fungal test growth. Analysis of sequences PKS and NRPS gene was conducted and identify of the antifungal subtances producing of selected isolate. The diversity analysis of cajuput isolates were using the fingerprinting was performed by rep- PCR with the BOXA1R primer. Targeting genes encoding PKS and NRPS were used to screen the antifungal biosynthetic potential of the selected isolates. Among 17 of a total 43 of isolates showing activity were screened for producing antifungi substances. The similarity of DNA fingerprints by BOXA1R repetitive sequences of the isolates were revealed two clusters based on index similarity 70% and 90%, respectively. Therefore, could be predicted that the isolates have high diversity relationships and show a positive correlation morphologically type with other isolates and ARDRA analysis. Analysis of the conserved KS domain sequences of the of PKS biosynthetic genes from the selected isolates was displayed highest sequence identity (59.03%) to geldanamycin from S. geldanamycininus AB430980. In the NRPS A-domain phylogeny, fragments of targeted gene appeared to be most closely related to the sequenced fragments of S.olivoverticillatus (AB432652). Phylogenetic analysis of selected isolate (GMR22) was revealed showed 96.38% similarity of S.vayuensis.The effect of various carbon and nitrogen sources of production antifungal was showed that starch as good carbon sources and KNO3 has been shown to be an excellent source of nitrogen for the growth and antifungal production of isolate, respectively. Analysis of the antifungal compound was conducted by reagent showed that the compound belong to the macrolide amide group. Meanwhile, analysis by LC-MS gave molecular ions at m/z 741.32 was predicted as a molecular weight of these antifungal compound. The subtances was including ansamycin group and the molecular structure was suggested similar with naphthomycin K. The MIC value of the compound were 62.5 Î¼g/mL against C. albicans.